The The Effect of The Ratio of Soy Milk to Whipping Cream on The Physical and Sensory Characteristics of Soy Milk Ice Cream Carrot Powder - Presilia, Yolanda; Artawan, I Putu Agus; Sastyari, Ni Made Elza Diah; Fitriyani, Lilalita Dian Ayu; Mahayani, Ni Putu Diah; Yosephine, Erline Evangeline; Dewi, Ni Putu Okta Diana; Magdalena, Magdalena; Tamalea, Rafi Renaldy (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2025)
Background: Plant-based ice cream made from soy milk has the potential to serve as a lactose-free functional food alternative; however, it often exhibits limitations in texture and sensory acceptance. The addition of whipped cream is expected to improve the physical and sensory characteristics of plant-based ice cream products. Purpose: This study aimed to evaluate the effect of different ratios of soybean milk to whipping cream on the physical and sensory characteristics of carrot and soybean milk ice cream and to determine the best formulation. Method: The research was conducted from may to July 2025 at the food processing laboratory, Faculty of Agricultural Technology, Udayana University. A Completely Randomized Design (CRD) was used with four treatments:P0 (100% Soybean milk:0% whipping cream), P1 (90%:10%), P2 (70%:30%) and P3 (50%:50%), each replicated three times. Observed variables included overrun, melting time, and sensory attributes such as aroma, texture, color, sweetness, mouthfeel, carrot flavor, soybean flavor, and overall acceptance, evaluated using scoring and hedonic tests by 30 semi-trained panelists. Result: Results showed that the soybean milk and whipping cream ratio significantly affected overrun, melting time, color, texture, mouthfeel, and overall acceptance. The highest overrun was obtained in P3(50.10%), while P0 recorded the lowest (14.41%). The melting time increased with higher whipping cream proportions, from 14.17 minutes in P0 to 110.81 minutes in P3. Sensory evaluation revealed significant differences in color, texture, mouthfeel, and overall acceptance, but no significant differences in aroma, sweetness, carrot flavor, and soybean flavor. Principal Component Analysis (PCA) indicated that P2 (70% soybean milk:30% whipping cream) produced the most preferred ice cream, characterized by a soft texture, creamy mouthfeel and the highest acceptance score. These findings suggest that optimizing the ratio of soybean milk and whipping cream can improve the quality and sensory properties of plant-based ice cream.